Human rights impact assessments as a new tool for development policy? - Fabiane Baxewanos; Werner Raza (Austrian Foundation for Development Research (ÖFSE), 2013)
Development policy affects human rights in manifold ways. For example, trade agreements can have an adverse impact on the rights to health or food by making essential medicines or goods less accessible or available. Or large-scale investment projects influence indigenous rights when they entail resettlement programs or the expropriation of traditional lands. Policy-makers have tried to tackle these issues by employing various impact assessment tools. These include, inter alia, the Sustainability Impact Assessments of EU trade agreements, and the impact assessments of projects by development finance institutions, which are commonly based upon the IFC Performance Standards. Traditionally, economic and environmental effects are at the centre of the existing tools, while social effects are only included to a lesser extent. This paper argues that the existing tools are insufficient for reasons that concern their legal status, their methodology and, in particular, their effectiveness. Human Rights Impact Assessments (HRIA) promise to cure some of these shortcomings. In the paper, the specific added-value of HRIAs, methodological approaches and challenges, and potential fields of application of HRIAs in development policy will be addressed.
Keywords: 330; Human Rights; Impact Assessment; Development Policy; Menschenrechte; Entwicklungshilfe; Entwicklungspolitik; Wirkungsanalyse; Welt